“By June, Everyone Would Have Died”: Historicising Humour during the Covid-19 Pandemic in Ghana - Charles Ofosu Marfo; Samuel Adu-Gyamfi; Confidence Gbolo Sanka; Benjamin Dompreh Darkwa; Lucky Tomdi (Modern Africa)
The impact of the COVID-19 pandemic on human interactions deeply affected the sense of humour of individuals. Using a social media research approach, this article analyses social media data in order to understand how social media users related with COVID-19. We sought to address the various events that generated humour among Ghanaians during the pandemic. The study reveals that the various instances of humour revolved around nose and/or face masks, terminologies and various social media posts. People neutralised their tensions and raised their humour with posts that flooded social media. This stemmed from the idea that people were mainly surprised at what they saw, watched or heard as they sought to release stress. We conclude that, owing partially to the creation of humour, the fear and tension associated with COVID-19 decreased with time among Ghanaians.